Assessment of the quality of professional life of nurses. - Aderval Aragão, José; Sant’Anna Aragão, Felipe Matheus; Sant’Anna Aragão, Iapunira Catarina; Costa Lourenço, Bárbara; Rodrigues Oliveira, Ana Clara; Conceição Porto, Luciano; Adário Marassi, Pedro Henrique; Ribeiro Guerra, Danilo; Correa Feitosa, Vera Lúcia; Prado Reis, Francisco (Brazilian Journal of Implantology and Health Sciences, 2023)
Context: The verification of quality of life at work (QLW) indices can provide information on factors that directly interfere with personal and collective satisfaction and motivation, with reflections on the excellence of the structure and service. Objective: To evaluate the quality of life at work of active nurses. Material and methods: descriptive and correlational, cross-sectional study with a quantitative approach, carried out with 104 nurses in the service of a tertiary public hospital, in the municipality of Aracaju/SE from August 2018 to July 2019. Results: Factors such as working conditions, safety and remuneration are degrading factors in the quality of life at work and these also have direct repercussions on health and the quality of nursing care provided. Conclusion: Low levels of quality of life at work have direct negative repercussions on nurses' health. It is suggested that further studies evaluate the measures taken by hospital institutions to investigate the effectiveness of quality of life at work in nursing.